Cultural moderation in entrepreneurial bricolage and orientation: Its impact on new product development - Abdul Samad Arief; Novita Rosanti; Mujahid Mujahid; Ilham Safar; Dodi Apriadi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
This study aims to examine the relationships between Entrepreneurial Orientation (EO), Entrepreneurial Bricolage (EB), and Local Culture (LC) and their effects on New Product Development (NPD) in Small and Medium Enterprises (SMEs) in Makassar. Specifically, the study investigates the mediating role of EB and the moderating role of LC. Data were collected from 200 SMEs using a structured questionnaire. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among the variables. The results show that EO has a significant positive effect on NPD, demonstrating the critical role of entrepreneurial orientation in fostering innovation. However, EB does not mediate the relationship between EO and NPD, indicating that bricolage may not be a necessary intermediary in this context. Additionally, LC has a direct positive impact on NPD, but it does not moderate the relationship between EO and NPD. The findings suggest that EO is a key driver of innovation, and efforts to enhance entrepreneurial behaviors should be prioritized by SMEs and policymakers. Although LC plays a role in innovation, it does not significantly influence the relationship between EO and NPD. This study contributes to the literature by providing empirical evidence on the complex relationships between entrepreneurial behavior, local culture, and product innovation in SMEs, particularly in culturally diverse settings.